Implementation of Differentiated Learning in Adjective Material for VII C Students of SMP Negeri 1 Ungaran - Prabowo, Rudy Kristyanto; Ariyanti, Nurul Umi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Differentiated learning is crucial in the independent curriculum to fulfill the diverse students’ needs. By adjusting instruction to individual learning styles and abilities, teachers can optimize learning outcomes. However, challenges such as limited resources and teacher capacity hinder its effective implementation. To overcome these challenges, teachers must employ effective classroom management, receive ongoing training, and foster collaboration with parents. By implementing differentiated learning, particularly in subjects like English, teachers can improve student engagement, motivation, and ultimately, their overall language proficiency. The aim of this research is to implement differentiated learning in adjective material in VII C students of SMP Negeri 1 Ungaran. The research method used was descriptive qualitative with research subjects in class VII C of SMP Negeri 1 Ungaran. The implementation was carried out for one month with a total of 34 students. In the initial stage of implementing differentiated learning, cognitive and non-cognitive diagnostic assessments are carried out. This diagnostic assessment obtains the results of grouping students based on learning styles and cognitive abilities. A total of 4 students were in the auditory group, 11 students were in the visual group, and 19 students were in the kinesthetic group. The result of implementing differentiated learning is that there is a positive increase in learning outcomes. In the upper class there was an increase of 33.33%, in the middle class there was no increase, and in the lower class there was a decrease of 30%